Urban and Rural Public Spaces: Development Issues and Qualitative Assessment - Micek, Michał; Staszewska, Sylwia (Bulletin of Geography. Socio-economic Series, 2019)
This paper presents selected issues related to the observation, assessment and development of urban and rural public spaces. Therefore, its initial part focuses on the specific nature of these spaces, and in particular on their functions and on problems in their development. It also describes features of urban and rural public spaces, which will be a prelude to the issue of qualitative assessment of the subject at hand. The method applied here can be used for the analysis of each urban space selected, thus strengthening the practical nature of this study. While over 80 public spaces have been analysed, the paper itself focuses only on the case studies that demonstrate the specific nature of the analysis that was carried out. The analysis process as a whole is only referred to in the summary.